Characterization and Classification of Cold Wave Conditions in Rocky Terrains of Jaisalmer District in Thar Desert - Kandpal, B K; Mertia, R S (Annals of Arid Zone, 2016)
The study was conducted to find out the occurrence of low temperature phenomenon in rocky terrain of Jaisalmer predominated by typical run off farming system called Khadin. Daily minimum temperature data for 26 years (1981-2006) were used to estimate mean minimum weekly temperature (Tmin) and absolute mean minimum weekly temperature (TLeast) from standard meteorological weeks 45 to 10. Based on Tmin and TLeast values the weeks were grouped into average/maximum chilling (<7°C), average/maximum near frost (<2°C) and average/maximum frost (<0°C) seasons, respectively, with five frequency distribution (very rare: Pi<5, rare: 5≤Pi≤10, infrequent: 10≤Pi≤20, frequent: 20≤Pi≤50 and very frequent: Pi≥50). The trend as well as correlation studies revealed that the winter climate at Jaisalmer is not entirely frostless. However, the reduction and subsequent rise in temperature generally is in accordance with movement of sun in southern hemisphere. Thus, cold wave/frost hazards can be predicted from simple quadratic regression model with significantly high precision. The chilling season is a regular phenomenon while near frost and frost events are very rare to infrequent throughout the study period except during weeks 52 to 3 when near-frost/frost events are frequently experienced due to the impact of western disturbances. Use of passive rather than active measures of protection will be economical in rainfed subsistence Khadin farming for such short and not so frequent near-frost/frost periods. Key words: Frost, near-frost, chilling, cold waves, frequency distribution, minimum temperature.